Perspective: Are animal scientists forgetting the scientific method and the essential role of statistics? - Black, J.; Diffey, Simon; Nielsen, S. (CSIRO Publishing, 2016)
Animal scientists and their funding organisations need to ensure investment in research is maximised by strict adherence to the scientific method and the rigorous design and analysis of experiments. Statisticians should be considered as equals in the research process, engaged from the beginning of research projects and appropriately funded. The importance of experimental design that accounts for factors affecting the primary experiment measurement is illustrated in two examples. One shows how failure to involve a statistician at the beginning of a project resulted in considerable waste of resources. Subsequent engagement of professional statisticians with rigorous experimental design and analysis led to greatly increased precision in the standard error of an estimate for the digestible energy content of cereal grains for pigs from 0.35 MJ/kg to 0.16 MJ/kg. The other example shows the effect of the percentage of diets replicated during pelleting and of the total number of pigs required in the experiment on theP-values associated with detecting a pairwise difference between two grains differing in digestible energy content by 0.33 MJ/kg. Decisions based on these relationships have animal welfare and resource allocation implications.